2022
DOI: 10.5802/crgeos.72
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of peralkaline rhyolitic magmas: pre- and syn-eruptive conditions of the Pantelleria system

Abstract: Pantelleritic magmas are low-viscosity peralkaline rhyolites which exhibit large differences in eruptive style (explosive to effusive). The processes that promote fragmentation and explosive eruptions of pantelleritic magma remain subject to debate, but undoubtedly variations of magma viscosity during magma ascent and degassing contribute to differences in eruptive style. Because crystallization can significantly influence magma rheology, we present a review of equilibrium and disequilibrium crystallization ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 118 publications
(269 reference statements)
0
3
0
Order By: Relevance
“…According to White et al [22], the observed mineral assemblages of these pantelleritic samples are compatible with redox conditions between ∆FMQ-1.5 and -0.5 for a temperature in the range 794-991 • C. Considering this f O 2 range, we can further constrain the magma temperature from olivine composition by using the equation of Romano et al [23], which relates fayalite content in olivine with f O 2 , T, and H 2 O melt . As reported by several studies [27][28][29][30][31], melt water content in pantellerite ranges between 2.5-4.5 wt%.…”
Section: Discussionmentioning
confidence: 68%
“…According to White et al [22], the observed mineral assemblages of these pantelleritic samples are compatible with redox conditions between ∆FMQ-1.5 and -0.5 for a temperature in the range 794-991 • C. Considering this f O 2 range, we can further constrain the magma temperature from olivine composition by using the equation of Romano et al [23], which relates fayalite content in olivine with f O 2 , T, and H 2 O melt . As reported by several studies [27][28][29][30][31], melt water content in pantellerite ranges between 2.5-4.5 wt%.…”
Section: Discussionmentioning
confidence: 68%
“…The viscosities of peralkaline silicic melts have been determined experimentally [Stevenson and Wilson, 1997, Stevenson et al, 1998, Di Genova et al, 2013, Stabile et al, 2016 and the results have been incorporated into various models of melt viscosity [Dingwell et al, 1998, Giordano et al, 2008. The results have confirmed that peralkaline silicic melts have lower viscosities than their metaluminous equivalents, by as much as 2-3 orders of magnitude, e.g., 10 10 -10 11 Pa•s, Stevenson and Wilson, 1997;10 9.6 -10 13.6 Pa•s, Stabile et al, 2016Stabile et al, , 2021. On Pantelleria, for example, the volcanological consequences of the low viscosities include the ubiquity of welded and rheomorphic pumice falls and high-grade to extremely high-grade ignimbrites [Rotolo et al, 2021].…”
Section: Viscositymentioning
confidence: 92%
“…Lanzo et al [2013] used the Papale et al [2006] model and a measured water content of 4.2 wt% to show that the Green Tuff, Pantelleria, had a saturation pressure of 65 MPa, equivalent to ∼2.5 km depth. According to Romano et al [2021] and Stabile et al [2021], the Papale et al model tends to slightly overestimate water solubility in such melt compositions. On the basis of new experimental determinations of water solubility in trachytic and pantelleritic rocks from Pantelleria, Romano et al [2021] estimated the depth of the felsic reservoirs on the island to deepen from 2.4 to 3.5 km.…”
Section: Geobarometrymentioning
confidence: 99%